Equity in family planning policies and programs in Uganda: conceptualization, dimensions and implementation constraints - Namuhani, Noel; Wanyenze, Rhoda K; Kiwanuka, Suzanne N ; Matovu, Joseph K B; Makumbi, Fredrick E (BioMed Central Ltd, 2024)
Equity is at the core and a fundamental principle of achieving the family planning (FP) 2030 Agenda. However, the conceptualization, definition, and measurement of equity remain inconsistent and unclear in many FP programs and policies. This paper aims to document the conceptualization, dimensions and implementation constraints of equity in FP policies and programs in Uganda. A review of Ugandan literature and key informant interviews with 25 key stakeholders on equity in FP was undertaken between April and July 2020. We searched Google, Google Scholar and PubMed for published and grey literature from Uganda on equity in FP. A total of 112 documents were identified, 25 met the inclusion criteria and were reviewed. Data from the selected documents were extracted into a Google master matrix in MS Excel. Data analysis was done across the thematic areas by collating similar information. Data were analyzed using thematic content analysis approach. A limited number of documents had an explicit definition of equity, which varied across documents and stakeholders. The definitions revolved around universal access to FP information and services. There was a limited focus on equity in FP programs in Uganda. The dimensions most commonly used to assess equity were either geographical location, or socio-demographics, or wealth quintile. Almost all the key informants noted that equity is a very important element, which needs to be part of FP programming. However, implementation constraints (e.g. lack of quality comprehensive FP services, duplicated FP programs and a generic design of FP programs with limited targeting of the underserved populations) continue to hinder effective implementation of equitable FP programs in Uganda. Clients' constraints (e.g. limited contraceptive information) and policy constraints (inadequate focus on equity in policy documents) also remain key challenges. There is lack of a common understanding and definition of equity in FP programs in Uganda. There is need to build consensus on the definitions and measurements of equity with a multidimensional lens to inform clear policy and programming focus on equity in FP programs and outcomes. To improve equitable access to and use of FP services, attention must be paid to addressing implementation, client and policy constraints.
Keywords: Equity in family planning, Dimensions of equity, Definitions of equity, Equity implementation constraints